Effects of lornoxicam and intravenous ibuprofen on erythrocyte deformability and hepatic and renal blood flow in rats - Arpacı H; Çomu FM; Küçük A; Kösem B; Kartal S; Şıvgın V; Turgut HC; Aydın ME; Koç DS; Arslan M (Dove Medical Press, 2016)
Hande Arpacı,1,* Faruk Metin Çomu,2 Ayşegül Küçük,3 Bahadır Kösem,4 Seyfi Kartal,4 Volkan Şıvgın,5 Hüseyin Cihad Turgut,6,* Muhammed Enes Aydın,5 Derya Sebile Koç,5 Mustafa Arslan5 1Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Ankara University, Ankara, 2Department of Medical Physiology, Faculty of Medicine, Kırıkkale University, Kırıkkale, 3Department of Medical Physiology, Faculty of Medicine, University of Dumlupınar, Kütahya, 4Department of Anesthesiology and Reanimation, Turgut Özal University Hospital, 5Department of Anesthesiology and Reanimation, Faculty of Medicine, Gazi University, 6Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Gazi University, Ankara, Turkey *These authors contributed equally to this work Background: Change in blood supply is held responsible for anesthesia-related abnormal tissue and organ perfusion. Decreased erythrocyte deformability and increased aggregation may be detected after surgery performed under general anesthesia. It was shown that nonsteroidal anti-inflammatory drugs decrease erythrocyte deformability. Lornoxicam and/or intravenous (iv) ibuprofen are commonly preferred analgesic agents for postoperative pain management. In this study, we aimed to investigate the effects of lornoxicam (2 mg/kg, iv) and ibuprofen (30 mg/kg, iv) on erythrocyte deformability, as well as hepatic and renal blood flows, in male rats.Methods: Eighteen male Wistar albino rats were randomly divided into three groups as follows: iv lornoxicam-treated group (Group L), iv ibuprofen-treated group (Group İ), and control group (Group C). Drug administration was carried out by the iv route in all groups except Group C. Hepatic and renal blood flows were studied by laser Doppler, and euthanasia was performed via intra-abdominal blood uptake. Erythrocyte deformability was measured using a constant-flow filtrometry system.Results: Lornoxicam and ibuprofen increased the relative resistance, which is an indicator of erythrocyte deformability, of rats (P=0.016). Comparison of the results from Group L and Group I revealed no statistically significant differences (P=0.694), although the erythrocyte deformability levels in Group L and Group I were statistically higher than the results observed in Group C (P=0.018 and P=0.008, respectively). Hepatic and renal blood flows were significantly lower than the same in Group C.Conclusion: We believe that lornoxicam and ibuprofen may lead to functional disorders related to renal and liver tissue perfusion secondary to both decreased blood flow and erythrocyte deformability. Further studies regarding these issues are thought to be essential. Keywords: rat, lornoxicam, iv ibuprofen, erythrocyte deformability, blood flow